2016
DOI: 10.4172/2161-038x.1000191
|View full text |Cite
|
Sign up to set email alerts
|

The Metformin-Induced Changes on BMI, TSH, and Thyroid Hormones Profile of Patients with Polycystic Ovarian Syndrome

Abstract: Objective: The aim of this prospective study was to investigate the effect of metformin on BMI, TSH, thyroid hormones profile, and some clinical symptoms in 32 women with PCOS. Methods: The patients received metformin at a dose of 500 mg/day which was gradually increased to 1500 mg/day and continued for 3 months. The level of BMI, TSH, T4, and T3 was measured at baseline, 3 months after treatment with metformin and 3 months after drug withdrawal. The association of metformin therapy with prevalence of constipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…In this research, we found that infertile PCOS patients had higher prevalence of subclinical hypothyroidism as compared to infertile control women. The verdicts of the current study are consistent with Nemati et al who establish that PCOS women had a substantially higher prevalence of TSH with a significantly higher TSH levels above the maximum limit of normal when compared to the control group [24,25]. Similarly, another study also found the higher mean serum TSH level in PCOS women than in same-age controls which concluded higher proportion of PCOS had subclinical hypothyroidism [26].…”
Section: Pcossupporting
confidence: 90%
“…In this research, we found that infertile PCOS patients had higher prevalence of subclinical hypothyroidism as compared to infertile control women. The verdicts of the current study are consistent with Nemati et al who establish that PCOS women had a substantially higher prevalence of TSH with a significantly higher TSH levels above the maximum limit of normal when compared to the control group [24,25]. Similarly, another study also found the higher mean serum TSH level in PCOS women than in same-age controls which concluded higher proportion of PCOS had subclinical hypothyroidism [26].…”
Section: Pcossupporting
confidence: 90%